Determinants of K1 and K4 Visits Coverage at Dungaliyo Community Health Center - Firdausi Ramadhani; Ririn Pakaya; FranningDeisi Badu (Aloha International Journal of Health Advancement (AIJHA), 2021)
This study aims to determine the factors related to the coverage of K1 and K4 visits in 2019. This study used analytical observational with a cross-sectional approach. The population were all mothers who have made K1 and K4 visits at Dungaliyo Community Health Center totaling 306 people, there were 158 people (51.6%) did not complete ANC and 148 people (48.4%) had complete ANC. The sampling technique used total population sampling and data collection using a questionnaire. Based on the results of statistical analysis using the Chi square test, it showed that the distance of health services, economic status, availability of transportation, and family support had a significant relationship with the coverage of K1 and K4 visits at Dungaliyo Community Health Center in 2019, p-value of the distance to health service = 0.000, economic status = 0.021, access to transportation availability = 0.000, family support = 0.000. Keywords: K1 and K4; distance to health service; economic status; access to transportation availability; family support.